2021
DOI: 10.3322/caac.21672
|View full text |Cite
|
Sign up to set email alerts
|

Addressing distress management challenges: Recommendations from the consensus panel of the American Psychosocial Oncology Society and the Association of Oncology Social Work

Abstract: Distress management (DM) (screening and response) is an essential component of cancer care across the treatment trajectory. Effective DM has many benefits, including improving patients' quality of life; reducing distress, anxiety, and depression; contributing to medical cost offsets; and reducing emergency department visits and hospitalizations. Unfortunately, many distressed patients do not receive needed services. There are several multilevel barriers that represent key challenges to DM and affect its implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 255 publications
(429 reference statements)
0
28
0
1
Order By: Relevance
“…Several randomized controlled trials have found that routine symptom monitoring is not only associated with improved quality of life, but also longer survival. Since 2015, the Commission on Cancer has mandated distress screening, requiring oncology providers to implement standardized screening and to document an action plan [ 47 , 48 , 49 ]. Systematic symptom screening can help identify patients who may benefit from specialist referral.…”
Section: Barriers and Facilitators To Timely Palliative Carementioning
confidence: 99%
“…Several randomized controlled trials have found that routine symptom monitoring is not only associated with improved quality of life, but also longer survival. Since 2015, the Commission on Cancer has mandated distress screening, requiring oncology providers to implement standardized screening and to document an action plan [ 47 , 48 , 49 ]. Systematic symptom screening can help identify patients who may benefit from specialist referral.…”
Section: Barriers and Facilitators To Timely Palliative Carementioning
confidence: 99%
“…Regarding psychologic measurements, not all instruments used were cancer-specific and abbreviated tools were used to allow the survey to be of reasonable length, which similar to clinical practice, might have decreased sensitivity and specificity. 29,30 Heterogeneity among phone interviewers, including providers that the patient might have interacted with as part of their care team previously, might have biased both how patients responded and which patients responded.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that significant distress is associated with negative health outcomes and screening for distress is associated with improved emotional well-being and fewer physical and practical concerns in previous HNC research [ 8 ], the uptake of distress screening in institutions remains limited. Improving health outcomes by screening for emotional distress requires attention to best practices from implementation science research [ 57 ]. Since positive screening must be followed by effective psychosocial care, an institution’s clinical capacity may determine which screening tool is optimal.…”
Section: Discussionmentioning
confidence: 99%